Sessile serrated adenomas and classical adenomas: an epigenetic perspective on premalignant neoplastic lesions of the gastrointestinal tract - Dhir, Mashaal (2011)
The diagnosis of sessile serrated adenomas (SSAs) is challenging, and there is a great deal of interobserver variability amongst pathologists in differentiating SSAs from hyperplastic polyps (HPPs). The aim of this study was (i) to assess the utility of epigenetic changes such as DNA methylation in differentiating SSAs from HPPs and (ii) to identify common methylation based molecular markers potentially useful for early detection of premalignant neoplastic lesions of gastrointestinal tract. A total of 97 primary patient adenoma samples were obtained from The Johns Hopkins Hospital pathology archive with IRB approval and HIPAA compliance. We analyzed the promoter associated CpG island methylation status of 17 genes using nested multiplex methylation specific PCR (MSP). Methylation of CDX2, hMLH1 and TLR2 was detected in SSAs and SSAs with dysplasia but not in HPPs. A subset of genes including EVL, GATAs (4 and 5), HIN-1, SFRPs (1, 2, 4 and 5), SOX17 and SYNE1 were methylated frequently in all premalignant gastrointestinal adenomas including tubular adenomas, villous adenomas, SSAs and SSAs with dysplasia but infrequently in non-premalignant polyps such as HPPs. Methylation of CDX2, hMLH1 and TLR2 may be of diagnostic utility in differentiating, histologically challenging cases of SSAs from HPPs. Genes such as EVL, GATAs, HIN-1, SFRPs, SOX17 and SYNE1, which are frequently methylated in all types of tested premalignant adenomas, may be useful as biomarkers in stool-based strategies for early detection of these adenomas and CRCs in future.